2015
DOI: 10.1186/s12933-015-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clopidogrel on platelet activity in patients with and without type-2 diabetes mellitus: a comparative study

Abstract: BackgroundAlthough antiplatelet therapy involving clopidogrel is a standard treatment for preventing cardiovascular events after coronary stent implantation, patients can display differential responses. Here, we assessed the effectiveness of clopidogrel on platelet function inhibition in subjects with and without type-2 diabetes and stable coronary artery disease. In addition, we investigated the correlation between platelet function and routine clinical parameters.MethodsA total of 64 patients with stable cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
3
34
0
1
Order By: Relevance
“…Under diabetic conditions, chronic inflammatory signaling in the vasculature sustains endothelial dysfunction, leukocyte infiltration, and a pro-thrombotic environment [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Under diabetic conditions, chronic inflammatory signaling in the vasculature sustains endothelial dysfunction, leukocyte infiltration, and a pro-thrombotic environment [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…These interesting findings could be partially explained by the fact that increased platelet reactivity was more likely seen in DM [4] and increased aspirin resistance in the elderly [5]. Following a sensitivity http://dx.…”
mentioning
confidence: 99%
“…Also in this study, as shown in table 2, difference of aggregation after dual antiplatelet therapy administration (∆t1-t2) is higher in non diabetic group than in diabetic group (3.30±2.91 vs 6.83±5.97, p=0.103). As mentioned in another research, diabetes mellitus can lead to platelet hyperreactivity (increased adhesion, activation, aggregation, and platelet turnover) (Ferreiro et al, 2011;Schuette et al, 2015). Thus, some researcher or clinician sometimes increase the maintenance dose of dual antiplatelet (Angiolillo et al, 2007;DiChiara et al, 2007), or used triple antiplatelet as maintenance dose after PCI (Lee et al, 2005).…”
Section: Resultsmentioning
confidence: 99%